Comparison of the Antioxidant Activity of Propolis Samples from Different Geographical Regions - Anna Kurek-Górecka; Şaban Keskin; Otilia Bobis; Rafael Felitti; Michał Górecki; Michał Otręba; Jerzy Stojko; Paweł Olczyk; Sevgi Kolayli; Anna Rzepecka-Stojko (Plants, 2022)
Propolis composition depends on several factors. The classification of propolis is based on its geographical location, color and agricultural characteristics. It is also classified according to the flora where the bees collect the resins, which represent the raw material for propolis production. Propolis possesses high antioxidant activity determined by its phenolic compounds. Due to diverse composition and possible impact on human health, eight samples of propolis were evaluated for their phenolic composition and antioxidant activity. Samples of Polish, Romanian, Turkish and Uruguayan origin propolis were used for phenolic spectrum determination using high performance liquid chromatography and photodiode array detection and in vitro DPPH and ABTS methods were used to determine the antioxidant activity of the extracts. PCA and HCA models were applied to evaluate the correlation between isolated polyphenols and antioxidant activity. The results confirmed variability in propolis composition depending on the geographical region of collection and the plant sources, and correlation between chemical composition and antioxidant activity. Results of PCA and HCA analyses confirm that Polish propolis is similar to that from different provinces of Romania, while Turkish and Uruguay are completely different. Polish and Romanian propolis belong to the poplar type. The assessed phenolic compounds of propolis samples used in the study are responsible for its antioxidant effect. The observed antioxidant activity of the analyzed samples may suggest directing subsequent research on prophylactic and therapeutic properties concerning cardiovascular, metabolic, neurodegenerative, and cancerous diseases, which are worth continuing.